Relationship between Soil Health Assessment and the Growth of Lettuce - Riwandi, .; Handajaningsih, Merakati (JOURNAL OF TROPICAL SOILS, 2011)
Soil health is very important point for plant growth which is measured by several indicators. The purposes of the research were to assess and to classify soil health Padang Betuah area of Bengkulu, and to compare between soil health indicators and lettuce plant performance indicators. Soils, consist of mineral and peat soils, were sampled using a soil random sampling technique. Lettuce plants were grown in polybags using sample soils. Both lettuce performance and soil health were assessed by calculating the percentage of total scores of lettuce plant or soil performance indicators which derived from variables observed. Soil variables for field evaluation included color, moisture content, texture, structure, compaction, land slope, organic matter, pH, amount of earthworm, erosion level, LCC (Legume Cover Crop), and vegetation performance. Soil variables for laboratory evaluation were pH, electrical conductivity (EC), total Carbon and Nitrogen, available-Posphorus, cation exchangeable capacity, basesaturation, and aluminum saturation. While, the variables for lettuce growth performance included plant height, numbers of leaf, degree of leaf greenness, plant fresh weight, and relative percentage of shoot : root ratio. The results of field and laboratory evaluation showed that soil health were categoried as a healthy soil and moderate healthy soil both for mineral and peat soils, respectively. Furthermore, similar categories were also obtained for evaluation of plant performance categories. No correlation was found between the soil performance indicatorcategory and the lettuce performance category.Keywords: Field indicator, laboratory indicator, lettuce growth indicator, soil health